Mineralogia e geoquímica da ocorrência de palygorskita de Alcântara, bacia de S. Luís-Grajaú, Maranhão - AMORIM, Kamilla Borges (2014)
The Alcântara Formation (S. Luis-Grajaú Basin, Alcântara region, northern Brazil) is mainly constituted by mudstones, sandstones and limestones. These lithotypes represent a progradacional succession of lagun/washover and tidal channel deposits that overlap huge shoreface deposits. The main purpose of this work is to carry out a mineralogical and geochemical characterization of the clay minerals association related to the pelitic rocks of the Alcantara Formation, specially the known palygorskite occurrences. One geological profile was sampled (eight samples) and described at the Baronesa beach (Alcântara city). The samples were submitted to mineralogical and chemical analysis by means of the following techniques: X-ray diffraction, X-ray fluorescence, thermal analysis (TG-DTA) and scanning electron microscopy. The results showed that the Baronesa Beach profile is mainly composed by sandstones at the base, followed by mudstones with intercalations of limestones. A wide clay mineral assemblage was described in a lagoon environment, with different contents of palygorskite, chlorite, illite, smectite and traces of kaolinite. Small amounts of dolomite, calcite and feldspars were also observed. The genesis of these minerals assemblage are mainly related to arid to semi-arid climatic conditions during the deposition period, with high evaporation rates. Two generations of palygorskite were described: (1) white macroscopic accumulations easily observed in the field and frequently described in the literature; and (2) massive accumulation, as the dominant mineral, in the upper muddy levels of the Baronesa Beach profile. This second generation is described for the first time in this work, and may constitute metric levels with potential economic interest.